Gold mineralisation and ore controls at the Clogau mine, Dolgellau, north Wales, United Kingdom - Dominy, Simon; Platten, I. (2012)
At a recorded production of 2·5 t Au and mill recovered grade of 17 g/t Au, Clogau is the largest and richest mine in the Dolgellau gold-belt and is the most prolific gold producer in the United Kingdom. The main period of production commenced in 1861 and ended in 1911, with intermittent production between 1983 and 2007. The principal gold-quartz bearing Main reef can be traced for about 3 km along strike, trending approximately NE-SW and dipping between 60uSE and 90uSE. The reef system pinches and swells, changes strike, and splits into a number of major and minor branches. Reef width is variable, ranging from 6 m to a few centimetres. The reef is internally complex and composed of swarms of narrow sub-parallel quartz veins separated by sheets of country rock. The gold-bearing vein segments within the composite reef package are discontinuous, though may locally possess bonanza grades running at 1000s g/t Au. The predictability of the gold-rich segments is poor, but has been shown to be related to presence of the Clogau Formation (black-shale), interactions of the reef fault with greenstone sills, and/or reef splitting to form discrete ore shoots. © 2012 Institute of Materials, Minerals and Mining and The AusIMM.